Political concepts : a reader and guide - Mackenzie, Iain M. (Edinburgh University Press, 2005)
Combines introductions with key readings in 20 core political concepts, from Civil Society to TolerationThis major textbook offers both an introduction to and key readings in twenty core political concepts. It blends original essays that survey debates and contact with up-to-date primary literature to provide students with an ideal collection for use on a wide range of courses in political studies.It reflects the broad nature of politics generally and political philosophy in particular from a perspective that highlights current debates and new trends surrounding many of the concepts we use to orient ourselves in the political world. The original essays and key readings together form an unparalleled introduction to the most dynamic and contested aspects of political studies that will be of interest to all who wish to engage with the issues animating current political life.Introduces the following conceptsCivil Society • Community • Democracy • Difference • Discourse • Equality • Globalisation • Human Nature • Ideology • Justice • Liberty • Multiculturalism • Power • Representation • Rights • The Body Politic • The Nation • The Rule of Law • The State • TolerationKey FeaturesThe only Reader and Guide in one volume on the subject of Political ConceptsCovers the core concepts taught on Politics coursesEach section includes a 5000-word introduction to the subject and two key texts - includes 40 of the most influential primary readings in contemporary political studiesAn original contribution from the editor on the multidimensional nature of political conceptsAn extensive bibliography and selected further reading to guide the student towards more in-depth researchIntroductions to each Part designed to help students connect different sections together.